PENGARUH PENDIDIKAN AGAMA DALAM PENGARUH PENDIDIKAN AGAMA DALAM KELUARGA DAN BUDAYA RELIGIUS SEKOLAH TERHADAP KECERDASAN EMOSIONAL SISWA MTs NU CANTIGI INDRAMAYU - Muthoharoh Muthoharoh (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
Emotional intelligence is one of the main elements in the family, and education began with the family, the family religious education in particular will be an formation of emotional intelligence in children or learners. In addition, the schools is seen as practical information about the effectiveness of teaching social and emotional intelligence. Of course if viewed practice in the field of religious education has a potential position with respect to the teaching of emotional intelligence. It would require religious culture in schools to support teaching in schools. The creation of religious atmosphere is done by way of practice, call (persuasive) in the school environment. This study aims to: (1) Describe the influence of religious education in families on high school students' emotional intelligence; (2) Describe the influence of religious culture of the school on students' emotional intelligence; (3) Describe students' emotional intelligence; (4) Would to find out the influence of religious education in families and religious culture of the school on high school students' emotional intelligence. The results showed that each independent variable and the dependent variable has a positive and significant correlation (0.559) or 31.24% and the religious culture of the school (0.567) or 32,15%. Taken together there is a significant relationship between religious education in the family with the religious culture of the school with emotional intelligence with the R value of 0.572, R2 of 0.327. This means that the percentage contribution of the influence of independent variables to the dependent variable of 33%.